PENERAPAN MODEL PEMBELAJARAN JIGSAW DALAM PEMBELAJARAN MATEMATIKA PADA MATERI OPERASI BILANGAN BULAT DI MI MIFTAHUL HUDA 02 PAPUNGAN KABUPATEN BLITAR - Siti Rizkiyah Nur handini; Faruuq Trifauzi (Program Studi Pendidikan Guru Sekolah Dasar FKIP Universitas Pasundan, 2026)
This research was motivated by the low level of students' active engagement and the prevailing negative stigma that mathematics is a difficult and abstract subject, particularly regarding integer operations material at MI Miftahul Huda 02 Papungan, Blitar Regency. This study aims to describe the planning, implementation process, and students' responses and learning transformations through the application of the Jigsaw cooperative learning model. A qualitative descriptive approach was employed, involving students and a mathematics teacher at MI Miftahul Huda 02 Papungan as research subjects. Data were collected through participant observation, in-depth interviews, documentation, and field notes, then analyzed descriptively through data reduction, data display, and conclusion drawing, with validity ensured through source and technique triangulation. The results indicate that: (1) learning planning was conducted thoroughly through the development of a Merdeka Curriculum teaching module integrating structured worksheets, material segmentation, heterogeneous grouping, and manipulative media such as expert cards and number lines; (2) the implementation of the Jigsaw model was effective, with Expert Group and Home Group activities shifting the learning paradigm toward a student-centered approach while the teacher acted as facilitator; and (3) the application of the Jigsaw model brought real changes in student activeness, self-confidence, and cooperation, creating a more lively, collaborative, and democratic learning atmosphere. This study is expected to serve as a reference for teachers in developing active and meaningful mathematics instruction in line with the characteristics of the Merdeka Curriculum.